2007
DOI: 10.1109/tap.2007.900258
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Method for the Computation of Green's Functions in Stratified Media

Abstract: Abstract-Closed-form Green's functions for unbounded planar stratified media are derived in terms of cylindrical and spherical waves. The methodology is based on a two-level approximation of the spectral-domain representation of Green's functions. This robust, efficient, and fully numerical approach does not call for an analytical extraction of "problematic" behaviors, such as the quasi-static terms and the surface wave poles, prior to the spectrum fitting. Instead, the spatial-domain Green's functions derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…2) is lossless, since this is the worst case scenario for the convergence of the series (1) [ (18)]. Also in this section, we will compare the CPU times employed in the computation of via (5) …”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) is lossless, since this is the worst case scenario for the convergence of the series (1) [ (18)]. Also in this section, we will compare the CPU times employed in the computation of via (5) …”
Section: Numerical Resultsmentioning
confidence: 99%
“…And that same 2-D Green's function with 1-D periodicity has also been used in the analysis of the scattering of plane waves from 1-D periodic arrays of lossy strips in free space [3]. Recently, several authors have shown that the nonperiodic Green's functions of multilayered media can be expressed in closed form as linear combinations of spherical and cylindrical waves in homogeneous media [4], [5]. According to this, the 3-D Green's functions of multilayered media with 2-D periodicity can be easily obtained in terms Manuscript of both 3-D homogeneous Green's functions with 2-D periodicity and 2-D homogeneous Green's functions with 2-D periodicity [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, application of one of the extrapolation techniques allows us to infer the limit value in (7) by calculating just a few partial integrals . As mentioned in the introduction, WA is a generalization of the Euler transformation, which instead of simple means uses weighted means of consecutive partial sums (8) where are the weights to be chosen. Since , (8) can be written in a following form: (9) Obviously, the optimal solution would come from the annihilation of the remainders of the linearly transformed sequence by imposing an appropriate ratio of the weights (10) In this point the WA method could be considered complete if the remainders were explicitly known, which is, unfortunately, not the case for the sequences of our interest.…”
Section: A Partition-extrapolation Methods Involving Wa Techniquementioning
confidence: 99%
“…Recently, a novel approach was proposed for extracting the surface wave poles by the rational function fitting method (RFFM) in the planar stratified media [17][18][19]. In this approach, the spectrum of the Green's functions was fitted via the RFFM, based on the vector fitting algorithm (VECTFIT) presented in [20,21], after the extraction of the quasistatic part of the spectrum.…”
Section: Introductionmentioning
confidence: 99%